Evaluation of Hanau's formula in determination of lateral condylar guidance: A clinical research study - Sanjay Vasant Bhawsar; Ashlesha Subhash Marathe; Sadekh Abdul Ansari (Wolters Kluwer Medknow Publications, 2015)
Statement of Problem: The accuracy and reliability of the methods used for programming the semi-adjustable articulators determine the accuracy in occlusion. The current recommended average settings using the Hanau's formula commonly used by clinicians is questionable, and thus reassessment is needed. This study was carried out to evaluate and compare the lateral condylar guidance: (1) Using the Hanau's formula and the computerized jaw tracking device (Kinesiograph). (2) On the right and left sides using both these methods. Materials and Methods: A total of 20 completely edentulous patients (14 male and 6 females) within 40-60 years of age were selected. Jaw relation was recorded followed by face bow transfer. Extraoral Gothic arch tracing was recorded; three protrusive records were obtained and condylar guidance was calculated. Lateral condylar guidance was then calculated using Hanau's formula, followed by the computerized jaw tracking device. A comparative evaluation was done of the obtained values. The same investigator worked with each of the study participants for the purpose of standardization. Results: The lateral condylar guidance values obtained using the Hanau's formula ranged from 14 to 17° while those obtained using the computerized K7 jaw tracking device ranged from 8 to 40°. Bennett angle values, obtained using the jaw tracking device and Hanau's formula showed statistically significant differences (P < 0.05) using paired t-test (at 95% confidence interval). Bennett angle values of the right and left sides found using the Hanau's formula were almost similar. Difference in the Bennett angle values of the right and left sides were found using the jaw tracking device. However, this difference was not statistically significant (P > 0.05). Conclusion: Based on the results, dentist and dental technicians should consider reassessing the current recommended average settings and use of the Hanau's formula for programming the semi-adjustable articulators.